Use of administrative healthcare claims to examine the effectiveness of trimethoprim–sulfamethoxazole versus fluoroquinolones in the treatment of community-acquired acute pyelonephritis in women - Carrie, A. G.; Metge, C. J.; Collins, D. M.; Harding, G. K. M.; Zhanel, G. G. (Journal of antimicrobial chemotherapy, 2004)
Objective: To evaluate the effectiveness of trimethoprim–sulfamethoxazole and fluoroquinolones in the treatment of community-acquired acute pyelonephritis. Patients and methods: We identified a population-based cohort of non-pregnant women aged 18–65 years, initially treated with trimethoprim–sulfamethoxazole or a fluoroquinolone for community-acquired pyelonephritis in an ambulatory care setting. Subjects were identified from a healthcare claims database in Manitoba, Canada for the period 15 February 1996 to 31 March 1999. Subsequent treatment failure, as evidenced by the provision of additional treatment up to 42 days post-diagnosis, was compared between the two treatments. Results: A total of 1084 women met inclusion criteria: 653 (60.2%) treated with trimethoprim–sulfamethoxazole and 431 (39.8%) treated with a fluoroquinolone. Treatment outcomes were affected by subject age. At age 20, treatment with a fluoroquinolone resulted in a reduced probability of treatment failure compared with trimethoprim–sulfamethoxazole (odds ratio, 0.56; 95% CI, 0.33–0.97). At age 60, there was no difference in the probability of treatment failure (odds ratio, 1.61; 95% CI, 0.82–3.16). No other subject characteristics impacted comparative effectiveness; however, several characteristics increased the odds of treatment failure irrespective of the initial antibiotic. These included: recent urinary tract infection (odds ratio, 2.07; 95% CI, 1.14–3.57), recent antibiotic use (odds ratio, 1.40; 95% CI, 1.00–1.96;), and a treatment duration of less than 10 days (odds ratio, 2.18; 95% CI, 1.59–2.99). Conclusion: Younger subjects (∼20 years) treated with fluoroquinolones were less likely to experience treatment failure than those treated with trimethoprim–sulfamethoxazole. Treatment durations of less than 10 days resulted in a higher probability of treatment failure regardless of the initial antibiotic.